Yoga as a Trauma-Informed Approach to Working with Clients - Dossaji, Amanda; Dickens, Kristen N.; Leachman, Kathryn; Deal, Lyndsay (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2025)
The practice of yoga has a long history of being used by practitioners for desired mental and physical benefits. The authors focused on the duality of this psychological and physical benefit when combining yoga with a traditional talk therapy group for individuals to process traumatic experiences. Group curriculum, procedures, and rationale are provided and reviewed. Yoga practices were implemented in this format as a form of expressive arts therapy for clients. This article outlines a therapeutic tool combining principles of yoga and talk therapy based on past research. This is not intended to be an empirical article; however, the information contributes to the current body of literature on yoga as a form of expressive arts therapy for clients with trauma-related presenting issues. The authors share anecdotal evidence of a counselor’s use of yoga in combination with group talk therapy and its perceived effectiveness on participants.